Five years of "Cirugía del Uruguay" - Praderi, Raúl C; Gómez Fossati, Carlos (Cirugía del Uruguay, 1975)
With this issue, CIRUGIA DEL URUGUAY celebrates its fifth consecutive year of regular and uninterrupted appearance and the also 45 years of publications of the Society of Surgery of Uruguay.